2019
DOI: 10.3390/polym11060965
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of Biodegradable Elastomer PEGylated Poly(glycerol sebacate) and Their Biomedical Application

Abstract: Poly(glycerol sebacate) (PGS), a biodegradable elastomer, has been extensively explored in biomedical applications for its favorable mechanical properties and biocompatibility. Efforts have been made to fabricate multifunctional PGS copolymer in recent years, in particular PGS-co-PEG (poly(glycerol sebacate)-co-polyethylene glycol) polymers. However, rare research has been systematically conducted on the effect of reactant ratios on physicochemical properties and biocompatibility of PGS copolymer till now. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 47 publications
(63 reference statements)
0
42
0
Order By: Relevance
“…These materials better support the mechanical requirements of initial implantation and they also provide desirable releasing profiles of bioactive factors. [63][64][65][66] According to recent studies, exosomes have been identified as a novel and effective therapy for skeletal tissue repair. Unfortunately, the common mode of administration for therapeutic exosomes was primarily through injection, in which therapeutic exosomes were unable to be retained at the desired site because they were inevitably rapidly cleared.…”
Section: Exosome/matrix Combination For Cartilage and Bone Tissue Engmentioning
confidence: 99%
“…These materials better support the mechanical requirements of initial implantation and they also provide desirable releasing profiles of bioactive factors. [63][64][65][66] According to recent studies, exosomes have been identified as a novel and effective therapy for skeletal tissue repair. Unfortunately, the common mode of administration for therapeutic exosomes was primarily through injection, in which therapeutic exosomes were unable to be retained at the desired site because they were inevitably rapidly cleared.…”
Section: Exosome/matrix Combination For Cartilage and Bone Tissue Engmentioning
confidence: 99%
“…Because of its tunable mechanical properties and remarkable biocompatibility, biodegradable elastomer poly(glycerol sebacate)-co-poly(ethylene glycol) (PEGS) has been widely used for various applications in tissue regeneration. [22][23][24][25] Specifically, our group previously found that the viscoelastic PEGS was beneficial to chondrocyte growth and extracellular matrix secretion and thus enhanced cartilage formation during bone regeneration. [26,27] Based on the above rationale, in this study, we endeavored to develop a novel injectable PAA-modified PEGS hydrogel (PEGS/PAA) to induce a hypoxia-based ECO for bone regeneration (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…With advantages of biocompatible, tailored release, prolonging circulation, and functionalizing with specific peptide targeting ligands or antibodies, polymers have been the most intensively explored materials in drug delivery systems. 86 -88…”
Section: Approaches Of Nanomedicines For Amlmentioning
confidence: 99%
“…With advantages of biocompatible, tailored release, prolonging circulation, and functionalizing with specific peptide targeting ligands or antibodies, polymers have been the most intensively explored materials in drug delivery systems. [86][87][88] Polymeric NPs could conjugate hydrophobic drugs by encapsulating to solid cores or water-soluble drugs by covalently attaching, which could control drug release, prolong circulation time, or reduce toxicity. [89][90][91][92] Polylactide (PLA) and poly(lactide-co-glycolide) (PLGA) are commonly used polymers at present.…”
Section: Passive Targeting Approaches In Amlmentioning
confidence: 99%